Carl Nielsen and Nancy Dalberg. Nancy Dalberg as Carl Nielsen’s Pupil, Assistant and Patron - Jensen, Lisbeth Ahlgren (Carl Nielsen Studies, 2005)
This article throws light on the connection between Nielsen and Nancy Dalberg, one of his less well-known composition pupils. She studied with Nielsen from c . 1912, and in the following years she composed several orchestral pieces and a symphony, which he conducted at her first composer’s concert. She was gradually drawn into Nielsen’s private circle of acquaintances, and she helped him with the fair copy of Aladdin and the orchestration of Springtime on Funen , following his indications in the draft score. This says something about his working methods when he was under time-pressure, but also about her expertise with regard orchestration. Nancy Dalberg’s own musical output is not extensive, and she did not make a great impact as a composer, but rather than explaining this by her being over-shadowed by Nielsen, the present article points to the fact that he was among those who supported her.